Distinct roles of GABA(A) and GABA(B) receptors in balancing and terminating persistent cortical activity. - Mann, E; Kohl, M; Paulsen, O (2009)
Cortical networks spontaneously fluctuate between persistently active Up states and quiescent Down states. The Up states are maintained by recurrent excitation within local circuits, and can be turned on and off by synaptic input. GABAergic inhibition is believed to be important for stabilizing such persistent activity by balancing the excitation, and could have an additional role in terminating the Up state. Here, we report that GABA(A) and GABA(B) receptor-mediated inhibition have distinct and complementary roles in balancing and terminating persistent activity. In a model of Up-Down states expressed in slices of rat entorhinal cortex, the GABA(A) receptor antagonist, gabazine (50-500 nM), concentration-dependently decreased Up state duration, eventually leading to epileptiform bursts. In contrast, the GABA(B) receptor antagonist, CGP55845 (50 nM to 1 microM), increased the duration of persistent network activity, and prevented stimulus-induced Down state transitions. These results suggest that while GABA(A) receptor-mediated inhibition is necessary for balancing persistent activity, activation of GABA(B) receptors contributes to terminating Up states.